Complex Studies of the Innovative Vortex Burner Device with Optimization of Design - Baubek A. Askar; Atyaksheva A. Aleksandra; Zhumagulov M. G.; Ponomareva K. V. Karina Vitaljevna; Kartzhanov N. Nurlan; Plotnikova I. V. Inna Vasilievna; Chicherina N. V. Natality Viktorovna (2021, 2021)
Title screen